2013
DOI: 10.1016/j.ijsu.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab therapy in the treatment of metastatic colorectal cancer: The future frontier?

Abstract: The use of cetuximab to conventional chemotherapy regimens may improve the efficacy of down-staging programmes, leading to more patients being offered potentially curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Several studies have shown the improvements in survival after the addition of anti-VEGF/EGFR[20-22]. Recently, a number of case series describing 10-year actual survivors after liver resection of CRLM have been published[23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the improvements in survival after the addition of anti-VEGF/EGFR[20-22]. Recently, a number of case series describing 10-year actual survivors after liver resection of CRLM have been published[23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, a chimeric mAb with approximately 152 kDa molecular weight, has a higher affinity to EGFR compared to its natural ligands, thereby inhibits the tumorigenesis effects of EGFR activation [73,74]. Cetuximab, combined with chemotherapy, is the standard practice for first-line treatment of RAS wild-type metastatic CRC patients [75].…”
Section: Cetuximabmentioning
confidence: 99%
“…Patients who do not respond to this first line therapy and have wild-type KRAS gene are sometimes given the anti-EGFR (epidermal growth factor receptor) therapy, Cetuximab or Panitumumab. However, the overall survival is only 4.6% to 12.3% for Cetuximab monotherapy and 6.9% to 18.9% for Cetuximab in combination with chemotherapy for colorectal cancer, and almost all therapy recipients eventually develop resistance to this second line therapy due to the selective pressure for activating mutation of proto-oncogene KRAS, downstream of the EGFR signaling pathway (6)(7)(8). Although immune checkpoint blockade therapy has some success with microsatellite-unstable CRCs, most (80%) sporadic CRCs are microsatellite-stable and refractory to such therapy (9).…”
Section: Introductionmentioning
confidence: 99%